2021
DOI: 10.1155/2021/3267201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sarcopenia and Its Effect on Postoperative Complications in Patients with Crohn’s Disease

Abstract: Background and Aims. Sarcopenia is a prognostic factor of outcomes for various diseases, but reports on sarcopenia in patients with Crohn’s disease (CD) are few. We aim to determine the prevalence of sarcopenia and assess the role of sarcopenia in postoperative complications in patients with CD at a tertiary referral center. Methods. Patients who underwent intestinal surgery for CD from January 2013 to October 2019 were retrospectively enrolled. The L3 skeletal muscle mass index (SMI) was used to identify sarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…It seemed that PNI was a better prognostic factor to predict postoperative complications of patients with CD. We also found that myopenia was an independent predictor of postoperative complications, which was consistent with our previous study ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…It seemed that PNI was a better prognostic factor to predict postoperative complications of patients with CD. We also found that myopenia was an independent predictor of postoperative complications, which was consistent with our previous study ( 25 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research had suggested that muscle loss was higher in males than females 11 . Sarcopenia was considered to be an age-related disease 2 . However, for CD patients with disease-related muscle loss, there was no statistical difference in age between the low and normal skeletal muscle groups.…”
Section: Discussionmentioning
confidence: 99%
“…The bone and skeletal muscle are vulnerable to be affected by the disease. Low muscle mass has been proven to be associated with adverse outcomes including the severity of CD, the presence of surgery related to CD, increase in the intestinal surgery-associated complications, and death 2 , 3 . CT is considered the gold standard technique for the detection of muscle quality and accurate assessment of body composition in patients with CD 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Galata et al obtained a sarcopenia prevalence of 70.4 % in 162 CD patients and proposed that the cut-off value for risk of postoperative adverse events should be an SMI of <41.5 cm 2 /m 2 in males and SMI of <31.8 cm 2 /m 2 in female patients as calculated by abdominal CT or MRI [ 11 ]. Zhang et al reported that the prevalence of sarcopenia was 27.4 % in 124 CD patients according to the cut-off previously reported by Martin et al [ 32 ], which is SMI <41 cm 2 /m 2 in females, SMI <43 cm 2 /m 2 in males with BMI <25 kg/m 2 , and SMI <53 cm 2 /m 2 in males with BMI ≥25 kg/m 2 [ 33 ]. These cut-off values of sarcopenia were useful to detect CD patients at higher risk of postoperative complication, but the data was mostly derived from patients of a Western genetic background.…”
Section: Discussionmentioning
confidence: 99%